Munasabah: Menelusuri konsep Al-Munasabah, Macam-macam Munasabah Qur’an dan manfaat mempelajari Munasabah Al-Qur’an - Saputri, Mahera Yogi (Maliki Interdisciplinary Journal, 2024)
Definition of munasabah in language is al muroqobah which means closeness, al musyakalah which means closeness, al musyakalah which means similarity and al muwafaqoh which means compatibility. Munasabah language itself comes from the word nasaba-yunaasibu-munasabatan which means close. There are several scholars who define the meaning of munasabah, az zarkasyi, manna al qathan, as suyuti, prof quraisy Shihab. Etymology is relationship between two or more parties, while in terms of knowledge about the meaning contained in the sequence of statements in the Qur'an. The purpose of this journal is that we the definition of munasabatul quran and the views of scholars about munasabah, know how the history of the emergence of munasabah quran, we can learn about the benefits of munasabatul quran. We can learn about the benefits of Munasabatul Quran. language, namely al muroqobah which means closeness, al musyakalah which means similarity and al muwafaqoh which means compatibility. Munasabah in language itself comes from the word nasaba-yunaasibu-munasabatan which means close. And there are nine kinds of qur'an musabatul. Briefly, the benefits of studying the munasabah of the Qur'an are, can knowing the correlation of a verse of the Qur'an, truly understanding the Qur'an well and correctly, avoiding mistakes in interpreting the Qur'an.